Relative Advantage of Mobile Medical Care (MMC) Aplication Services at Hospital - Robiatul Febriyani; Ilmi Usrotin Choiriyah (Indonesian Journal of Public Policy Review, 2023)
The purpose of this study is to determine, describe and analyze the relative advantages of Mobile Medical Care (MMC) services. Qualitative descriptive research method through interviews, observation and documentation. Determination of informants was carried out by purposive sampling method which involved the Head of Medical Records, IT officers, KAURBIN and users of Mobile Medical Care (MMC) application services. Data analysis techniques using Miles and Hubberman through data collection, data reduction, data presentation, drawing conclusions. The results of this study indicate that the service of this relative advantage is indicated by the speed of response to each incoming registration.